2014
DOI: 10.1162/jocn_a_00484
|View full text |Cite
|
Sign up to set email alerts
|

Task- and Experience-dependent Cortical Selectivity to Features Informative for Categorization

Abstract: In this study, we bridge the gap between monkey electrophysiological recordings that showed selective responses to informative features and human fMRI data that demonstrated increased and selective responses to trained objects. Human participants trained with computer-generated fish stimuli. For each participant, two features of the fish were informative for category membership and two features were uninformative. After training, participants showed higher perceptual sensitivity to the informative dimensions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…In contrast to these studies, two more recent category learning experiments in humans have found evidence of tuning changes to task-relevant dimensions in the occipitotemporal cortex using fMRI-adaptation (Folstein et al, 2013;van der Linden et al, 2014), as well as strong tuning to category in the prefrontal cortex (van der Linden et al, 2014). The basis of the contrasting results is not entirely clear, but it is possible that the composite nature of the form changes in earlier studies made it more difficult for participants to attend to single relevant form dimensions which could have aided earlier occipitotemporal plasticity.…”
Section: Task-dependence Of Changes To Neural Representations That Acmentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast to these studies, two more recent category learning experiments in humans have found evidence of tuning changes to task-relevant dimensions in the occipitotemporal cortex using fMRI-adaptation (Folstein et al, 2013;van der Linden et al, 2014), as well as strong tuning to category in the prefrontal cortex (van der Linden et al, 2014). The basis of the contrasting results is not entirely clear, but it is possible that the composite nature of the form changes in earlier studies made it more difficult for participants to attend to single relevant form dimensions which could have aided earlier occipitotemporal plasticity.…”
Section: Task-dependence Of Changes To Neural Representations That Acmentioning
confidence: 96%
“…Repetition suppression shares many of the empirical characteristics of repetition priming: it is relatively automatic, even occurring in animals under anesthesia (e.g., Miller, Gochin, & Gross, 1991); it can be long-lasting following a small number of stimulus exposures (up to several days, e.g., van Turennout et al, 2000van Turennout et al, , 2003, although effects are strongest with little or no delay (e.g., Grill-Spector & Malach, 2001;Jiang et al, 2000;van Turennout et al, 2003); it is robust to small changes in stimulus form and/or task, with the largest effects when stimuli and tasks are identical across repetition (e.g., Horner & Henson, 2008;Koutstaal et al, 2001;Lueschow, Miller, & Desimone, 1994). Repetition suppression in humans is typically observed throughout the neocortex within regions that are engaged by the task being performed (see Schacter & Buckner, 1998;Wiggs & Martin, 1998, for reviews).…”
Section: The Puzzle Of Repetition Suppressionmentioning
confidence: 97%
See 3 more Smart Citations